Konsep Pendidikan Islam Menurut Persfektif Ibnu Sina - Solihin Solihin (LPPM STAI La Tansa Mashiro, 2014)
The science of Islamic education is an ideal education. Islamic development grows and develops in line with the existence of da'wah. Islamic education continues to change both in terms of curriculum and in terms of Islamic education institutions. science will not progress further without research and renewal. Research efforts have actually been carried out by past scholars, including educational issues. Islamic education, which has always been more visible as an educational practice, and not as a science in the sense of science that has its own discussion structure and research methodology. This is different from the science of education in general whose growth and development is much faster than the science of Islamic education. Various aspects related to education in general, ranging from problems of philosophy of education, curriculum, learning methodology, technology education, to the educational environment. The purpose of this study was to find out the concept of Islamic education in Ibn Sina's perspective. The method in this study is a naturalistic qualitative method, this method used by Karen in accordance with the purpose of the study, namely to describe naturally. The results showed that the full name of Ibn Sina was Abu ‘Al-Husain ibn‘ Abd Allah ibn Hasan ibnu ‘Ali ibn Sina. Ibn Sina was born in Afsyna near Bukhara in 980 AD and died in 1037 AD at the age of 58. His body was buried in Hamadzan. Ibn Sina's theory in education must be directed at the development of all the potential a person has towards his perfect development, namely physical development, intellectual and character Ilmu pendidikan islam adalah pendidikan yang sangat ideal. Perkemabangan islam tumbuh dan berkembang sejalan dengan adanya dakwah. Pendidikan islam terus mengalami perubahan baik dari segi kurikulum maupun dari segi lembaga pendidikan islam. ilmu tidak akan bertambah maju tanpa adanya penelitian dan pembaharuan.upaya penelitian sebenarnya sudah dilakuakan para ulama masa lalu, termasuk masalah pendidikan. Pendidikan islam yang selama ini ada lebih tampak sebagai sebuah praktek pendidikan, dan bukan sebagai ilmu dalam arti ilmu yang memiliki struktur bahasan dan metodologi penelitiannya tersendiri. Hal ini berbeda dengan ilmu pendidikan pada umumnya yang pertumbuhan dan perkembangannya jauh lebih pesat dibandingkan dengan ilmu pendidikan islam. Berbagai aspek yang berkaitan dengan ilmu pendidikan pada umumnya, mulai dari masalah filsafat pendidikan, kurikulum, metodologi pembelajaran, teknologi pendidikan, hingga lingkungan pendidikan. Tujuan dalam penelitian ini adalah untuk mengetahui konsep pendidikan islam dalam persfektif ibnu Sina. Metode dalam penelitian ini adalah metode kualitatif naturalistic, metode ini digunakan Karen sesuai dengan maksud penelitian, yakni untuk menggambarkan secara alami. Hasil penelitian didapatkan bahwa Nama lengkap Ibnu Sina adalah Abu ‘Al-Husain ibnu ‘Abd Allah ibn Hasan ibnu ‘Ali ibn Sina. Ibnu Sina dilahirkan di Afsyna dekat Bukhara pada tahun 980 M dan meninggal pada tahun 1037 M dalam usia 58 tahun. Jasadnya dikebumikan di Hamadzan. Teori Ibnu Sina dalam pendidikan harus diarahkan pada perkembangan seluruh potensi yang dimiliki seseorang kea rah perkembangannya yang sempurna, yaitu perkembangan fisik, intelektual dan budi pekerti.